Whole-cell mediated 11 beta-hydroxylation on the basic limonoid skeleton by cunninghamella echinulata - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2015)
Regio- and stereoselective 11 beta-hydroxylation was achieved on the basic limonoid skeleton through microbial transformation. Whole cells of Cunninghamella echinulata efficiently converted basic limonoids such as epoxyazadiradione, azadiradione, and gedunin to their 11 beta-hydroxy analogues as the sole metabolite. Fermentation conditions affecting the efficiency (96%) of biotransformation including substrate concentration, incubation period, pH, and temperature were optimized. The position and stereochemistry of hydroxyl functionality on the isolated metabolites were established through extensive spectroscopic and spectrometric studies (1D, 2D NMR, ESI-MS, and MS/MS).